Thermal behaviour study of solid state compounds of manganese (II), zinc (II) and lead (II) with cinnamic acid - Carvalho, MAD; Ionashiro, M. (Editora Unesp, 1998)
Compounds of cinnamic acid with manganese, zinc and lead have been prepared in aqueous solution. Thermogravimetry, derivative thermogravimetry (TC, DTG), differential scanning calorimetry (DSC), X-ray diffraction and complexometry have been used in the characterization as well as in the study of the thermal stability and interpretation concerning the thermal decomposition.
Keywords: manganese; zinc; lead; cinnamic acid; thermal decomposition